Anticuerpos antipertussis en la población infantil de la provincia Holguín. - Rodriguez González, Daisy P.; Zuazo Silva, Jorge L.; González Betancourt, María I.; de los Reyes Valdés Hernández, María (Revista Cubana de Pediatría, 2024)
Búsqueda de aglutininas antipertussis.